The Bubble Painting Activity as a Science Teaching Media to Improve Cognitive Skill in 4-5 Years Old Children - Rahayu, Sri Setiyo; Waluyo, Edi (Indonesian Journal of Early Childhood Education Studies, 2015)
Science learning in Kindergarten is still exist and integrated with other subject in every topic. Science introduction and learning which are implemented in Kindergarten have characteristic as integrated learning, so science learning is integrated with other development. The development of science learning in children is included other development field has very important role to place base ability and form expected human resources. Various nature symptoms such as rain, wind, thunder, fire, breeding animal, and bear fruit plant also get children’s interest. Those objects can be learnt by scientific method which should be simplified for Kindergarten student. Simple observation, exploration, and experimentation can be done by children. Children can do other science processes like mixing primary color, measurement, doing classification, etc. Science product for children is dominant in form of knowledge about facts and symptoms of nature. The aim of this study is to know method and result of Bubble Painting media usage in improving the cognitive ability of children age 4-5 years old in TK Pertiwi 49 Semarang. This study did in TK Pertiwi 49 Semarang with sample all of the students in group A with amount 24 students. The study steps including pre-study, data collection, and data analysis. Data collection methods used are observation and documentation. According to the observation and documentation result, it can conclude that using the method of Bubble Painting media is by mixing yellow, red, or blue, we can get another color like orange, green, and purple. In Bubble painting games, there are; mixing primary color activity until produces new color, measuring detergent, the introduction of substance characteristic (liquid, solid, gas). Learning process using Bubble Painting in children age 4-5 years old in TK Pertiwi 49 Semarang could improve cognitive ability whether in science knowledge concept and the concept of shape, color, size, and model. Children cognitive ability improvement also increase from 69,37 to 78,19, the result of T-test is 78,19% (30,31 > 2,013). From that result, we can conclude there is a significant difference between children cognitive ability before and after using Bubble painting media.How to citeRahayu, S., & Waluyo, E.. (2015). The Bubble Painting Activity as a Science Teaching Media to Improve Cognitive Skill in 4-5 Years Old Children. Indonesian Journal Of Early Childhood Education Studies, 4(1), 42-45. doi:10.15294/ijeces.v4i1.9452